2010
DOI: 10.1902/jop.2010.090540
|View full text |Cite
|
Sign up to set email alerts
|

Root‐Coverage Procedures for the Treatment of Localized Recession‐Type Defects: A Cochrane Systematic Review

Abstract: SCTGs, coronally advanced flaps alone or associated with other biomaterial, and GTR may be used as root-coverage procedures for the treatment of localized recession-type defects. In cases where root coverage and gain in keratinized tissue are expected, the use of SCTGs seems to be more adequate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
345
0
27

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 276 publications
(387 citation statements)
references
References 123 publications
15
345
0
27
Order By: Relevance
“…However, neither of these techniques has been shown to demonstrate any significant benefit over traditional grafting procedures. 22 …”
Section: The Use Of Allografts and Xenografts In Management Of Gingivmentioning
confidence: 99%
See 3 more Smart Citations
“…However, neither of these techniques has been shown to demonstrate any significant benefit over traditional grafting procedures. 22 …”
Section: The Use Of Allografts and Xenografts In Management Of Gingivmentioning
confidence: 99%
“…25 The mean percentage root coverage achieved with subepithelial connective tissue grafts has been shown to vary between 65-98%. 22,[26][27][28][29] The number of sites showing complete root coverage varies between 18-87%. 22,28 Chambrone et al 30 suggested that connective tissue graft could be considered to be the gold standard grafting procedure.…”
Section: Prognosismentioning
confidence: 99%
See 2 more Smart Citations
“…A recent systematic review found that overall a better percentage of complete and mean root coverage was seen in recession defects less that 4 mm. 9 The mean root coverage achieved with a laterally repositioned flap and the double papilla flap have shown to vary between 34-81% and complete root coverage varies between 40-50% of sites. 25,26 With these procedures there is a risk of donor site recession particularly with the laterally repositioned flap of approximately 1 mm.…”
Section: Prognosismentioning
confidence: 99%